Pancreatic cancer cachexia: a review of mechanisms and therapeutics - Tan, Carlyn R.; Jamil, Laith; Yaffee, Patrick; Tuli, Richard; Nissen, Nick; Lo, Simon; Pandol, Stephen J.; Hendifar, Andrew E. (Frontiers in Physiology, 2014)
Over the last decade, we have gained new insight into the pathophysiology of cachexia associated with pancreatic cancer. Unfortunately, its treatment is complex and remains a challenge. Pancreatic cancer cachexia is a multifactorial syndrome characterized by uncompensated adipose tissue and skeletal muscle loss in the setting of anorexia that leads to progressive functional impairment. This paper will review the current concepts of pancreatic cancer cachexia, its assessment and pathophysiology as well as current and future treatments. The successful management of pancreatic cancer cachexia will likely require a multimodal approach that includes nutritional support and combination pharmaceutical interventions.